2012
DOI: 10.3109/14767058.2012.663824
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival in pre-viable preterm premature rupture of membranes

Abstract: Pre-viable PPROM has a poor prognosis, though modern neonatal management techniques may improve survival in late pre-viable PPROM. The predictive model generated from this consecutive case series of this rare condition provides valuable data for counselling patients with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
6
25
0
Order By: Relevance
“…Although the role of amniotic fluid as a predictor of mortality has recently been questioned [9,18], our data, including a larger number of women, and in line with previous reports [1,4,12,30,31], suggest that the presence of a lower LVP at admission is associated with a significantly higher rate of perinatal mortality.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although the role of amniotic fluid as a predictor of mortality has recently been questioned [9,18], our data, including a larger number of women, and in line with previous reports [1,4,12,30,31], suggest that the presence of a lower LVP at admission is associated with a significantly higher rate of perinatal mortality.…”
Section: Discussionsupporting
confidence: 80%
“…However, the definition of prolonged oligohydramnios remains unclear [2,4,9,10,15,16,18]. A precise definition of prolonged oligohydramnios would help obstetricians and parents in the decision-making process regarding the perinatal mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers have been published describing fetal and neonatal outcomes after PROM before 24 weeks gestation . It is difficult to compare their results, however, due to variations in the characteristics of study populations, clinical management strategies used, and reported outcomes.…”
mentioning
confidence: 99%
“…Survival rates reported in the literature on pregnancies complicated by PROM before 24 weeks vary significantly. Studies published in the last decade report that 26% to 56% of these pregnancies result in the birth of a neonate who survives to discharge . The quoted proportion of babies admitted to a neonatal nursery who survive to hospital discharge varies from 62 to 79% .…”
mentioning
confidence: 99%